A SOCIOPRAGMATIC ANALYSIS OF THE SPEECH ACT OF REQUESTING IN LOCAL ENGLISH COURSEBOOKS - Nurdiana Nurdiana Nurdiana (Universitas Bunda Mulia, 2023)
The speech act of requesting is a speech act commonly found and used in daily conversations. It is an intriguing research topic of pragmatics, particularly pragmatics in materials development, which is a sub-topic of language teaching. Earlier studies of pragmatics in language teaching reported that English teachers tend to look down on pragmatic aspects when teaching the language, including being ignorant of sociopragmatic information about language use in English coursebooks. For this reason, this paper discusses the findings of a sociopragmatic analysis in a local English coursebook. A content analysis employing pragmatic and sociopragmatic theoretical frameworks and a pragmatic judgment task by a native speaker of American English was carried out to investigate the sociopragmatic information in the course book. Results indicated that it did not contain an adequate amount of sociopragmatic knowledge indicating sociopragmatic failure. Thus, it implies that the coursebook may not be reliable language input for pragmatic competence improvement.